Comparison of analgesic requirements in robot-assisted versus conventional laparoscopic abdominal surgeries - Athira Suresh Mangalath; Lakshmi Kumar; Ambreen Basheer Sawant; Rajesh Kesavan; Greeshma Ravindran; Rajan Sunil (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Robot-assisted surgery is advantageous in the precision of tissue handling and shorter postoperative recovery. We compared postoperative analgesic requirements in laparoscopic versus robot-assisted surgery in the first 24 h as our primary objective. The secondary outcomes were extubation on table, time to ambulation, and length of ICU stay. Material and Methods: After approval from the ethics committee 48 patients undergoing either laparoscopic (group L [n = 24]) or robotic abdominal surgery (group R [n = 24]) were evaluated for analgesic requirements postoperative targeting a numerical rating scale ≤3 in a prospective comparative study. Postoperative patients were allotted to a three-tier pain management, level 1 comprising paracetamol 1 g intravenously every 8 h, level 2, 1.5 mg/kg tramadol every 8 h, and level 3 fentanyl 0.5 μg/kg. The total analgesic consumption in the first 24 h was calculated for each group. Statistical analysis was performed using the Chi-square test and Mann-Whitney U test. Results: Age, weight, and types of surgery were comparable between the groups. The intraoperative opioid use was comparable between both groups but the duration of surgery was longer in group R. Postoperative analgesic requirements were significantly less in group R (P = 0.024) and the length of ICU stay was shorter (P < 0.05). The time to ambulation was significantly shorter in group R patients (P < 0.001). Conclusion: Analgesic requirements were significantly less in robot-assisted laparoscopic surgery in the first 24 h. The time to ambulation and length of ICU stay were shorter in the robot-assisted group in comparison to the laparoscopic group.